Mbojo: Lion Attacks on People West of Tarangire N.P., Tanzania - Skuja, Mike (My University, 2001)
Between the days of November 11th and November 26th, 2000 I conducted a study of problems villagers were experiencing with lions in northern Tanzania. The study took place in the villages of Sangaiwe, Sarame, Chern Chemu, Mawemairu, Kiongozi, Gichameda, and Kisangaji. These villages all lie west of Tarangire National Park, between the Sangaiwe and Mbulu hills. Data collected in the field was concerned primarily with documenting the problem and work done at UW-Madison with analyzing the data and establishing land-use trends. Field interviews were undertaken with the village chairmen, secretaries, and elders. Results showed that lions have been preying sporadically on domestic animals since roughly the establishment of the villages, and as prey steadily disappeared, they shifted towards domestic stock as a steady and reliable source of food. When lions cannot hide in vegetation to hunt wildlife due to a drought, they often migrate into the villages in search of domestic food. The phenomena of man-eating started only recently in 1997. Results and field observations indicate that lions are still found in the area in the first place because of favorable habitat, a water source, and an adequate prey base in the form of domestics. The reasons for the recent man-eating behavior varies slightly depending on the geographical area in question, but in general, there has been a lot of immigration in the past few years putting the settlement ever closer to the forest which was, or recently became, void of wildlife due to drought. The closer settlement to the forest allows the lions to see more clearly where the domestic animals are taken for the night, and with a decline in pastoralism and the advent of villagers grazing their animals closer to the villages than before, the lions have taken to roaming about the villages more, making chance contact with humans more likely, and often fatal.
Pictures; Tables; Maps; Figures; Bibliography
Keywords: Tanzania; Lions; Mbojo